Management and outcome of Scrotal Abscess (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: An abscess that is either superficial or intrascrotal is known as a scrotal abscess (see illustration below). Infected hair follicles, infections from scrotal lacerations, or small scrotal procedures are the causes of the superficial scrotal abscess. An internal pus collection in the scrotum is referred to as a scrotal abscess. The skin pouch that houses the testicles is known as the scrotum. There are numerous potential causes of this illness. It could result from a bacterial infection in the urethra or bladder that is left untreated. Scrotum infection is a possibility. In addition, sexually transmitted illnesses may be the cause of the syndrome (STDs). Chlamydia and gonorrhea are a couple of STD examples. A supportive tumor that affects the outermost layers of the scrotal wall and is surrounded by erythema is known as a scrotal abscess. A small pustule or papule may typically enlarge over time with increased pain, indurations, or fluctuance as part of the history. Fever and constitutional symptoms are typically absent.Patient History: -Patient 36-year-old male admitted to the hospital patient was apparently alright 3 days back when he started complaining of pus coming out of the scrotum 3 days it was sudden in onset with progressive it was associated with pain, radiating, aggravated by physical activity and not relieved by medication. Presenting Complaints and Investigation: The patient 36-year-old male admitted to the hospital with pus coming out of his scrotum, patient was apparently alright 3 days back when he started complaining of pus coming out of his scrotum since 3 days it was sudden in onset with progressive it was associated with pain, on radiating, aggravated by physical activity and not relieved by medication. Hb-13.4, MCHV-33.6,MCV-83.6,MCH-28.1,Total RBC Count-4.76,Total Platelet Count-3.24,HCT- 39.8,Monocytes-03,USG- Right sided epididymitis with changes of cellulitis in right inguinal region reactive right-sided inguinal lymphadenopathy. Past History: No prior hospitalizations or medical or surgical illnesses in the past. The main diagnosis, therapeutic intervention, and outcome: secondary suturing secondary to incision and drainage of scrotal abscess, Treatment- injceftriaxone1gmivbd, injpiptaz4.5gmivtds, injdoxycycline10mgbd,t.doxyxyline100mgbd,t.chymoralforte2tabstds,t.zifi200mgbd,t.urgendolpbd,t.pantoprazole40mgod,t.limceeod,t.supradynod, t. dolo 650 mg od Conclusion: In order to stop the condition from progressing, it is crucial to remove abscess and pus as soon as possible and provide rapid diagnosis and treatment. Opportunities to improve results are provided through early detection and intervention.